Warfarin Hyper-Responsiveness in a Female Patient with Deep Venous Thrombosis and CYP2C9*1*3 and VKORC1 -1639 AA Genotypes - يوسف, لمى; الجمالي, مجد; الديبان, وئام (Latakia University Journal -Medical Sciences Series, 2021)
Warfarin hyper-responsiveness unexplained by clinical and/or environmental factors represents a dilemma to both patients and health care providers, and necessitates the investigation of underlying genetic factors mostly linked to the two genes encoding key enzymes in warfarin’s pharmacokinetics (CYP2C9) and pharmacodynamics (VKORC1). This report documents the case of a 22-year-old patient who received anticoagulation therapy for deep venous thromboembolism after cesarean section, and presented with hypersensitivity to regular dose of warfarin (35 mg/week) manifested by elevated International Normalized Ratio INR >4 in the fourth day after warfarin commence. The dose was tapered (17.5, 12.5, and 10 mg/week) over a period four months interrupted by episodes of INR >4 and epistaxis, and ultimately reached an effective and safe dose at 7.5 mg/week. Genotype analysis later using standard sequencing of specific PCR products revealed homozygosity (AA) of VKORC1 (-1639G>A) and heterozygosity of the *3 allele (CYP2C9*1*3). This extremely low dose (7.5 mg/week) is in accordance with that recommended by genotype-guided algorithms for carriers of these genotypes. This report sheds light on the first documented case of genetically explained hyper-responsiveness to warfarin in Syria, and highlights the significance of pharmacogenetics in optimization of warfarin therapy.